2017
DOI: 10.1103/physreva.95.012326
|View full text |Cite
|
Sign up to set email alerts
|

Role of entanglement in calibrating optical quantum gyroscopes

Abstract: We consider the calibration of an optical quantum gyroscope by modeling two Sagnac interferometers, mounted approximately at right angles to each other. Reliable operation requires that we know the angle between the interferometers with high precision, and we show that a procedure akin to multiposition testing in inertial navigation systems can be generalized to the case of quantum interferometry. We find that while entanglement is a key resource within an individual Sagnac interferometer, its presence between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Even for large photon losses in phase imaging applications, simultaneous estimation schemes can provide a constant factor advantage over individual schemes. This has seen a surge of recent work focused on yielding quantum enhanced sensing from simultaneous estimation of multiple parameters 109,113,131,[135][136][137] .…”
Section: Simultaneous Versus Sequential Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for large photon losses in phase imaging applications, simultaneous estimation schemes can provide a constant factor advantage over individual schemes. This has seen a surge of recent work focused on yielding quantum enhanced sensing from simultaneous estimation of multiple parameters 109,113,131,[135][136][137] .…”
Section: Simultaneous Versus Sequential Estimationmentioning
confidence: 99%
“…However, in section IV H we saw recent work that demonstrate non-entangling strategies to achieve the same scaling as entangled probes 92 . Beyond a few counter examples that have reported too much entanglement as detrimental 86 , little research to date has addressed the question when and how much entanglement is necessary as a resource in order to saturate fundamental quantum precision bounds 137 . Distributed quantum sensing holds the promise to demonstrate the utility of entanglement and elucidate its contribution in providing precision enhancements.…”
Section: Distributed Quantum Sensingmentioning
confidence: 99%
“…It has already been shown that in a multimode (multipath) interferometer, measuring all phases simultaneously with a mode-entangled state can enhance the precision [9]. However, in stark contrast to this, in other applications of quantum metrology multimode entanglement can be detrimental, such as when measuring coupled phases [12] or when loss is considered [13]. Furthermore, from a practical point of view, large multimode-entangled states are notoriously difficult to produce and are fragile to experimental imperfections and photon losses.…”
Section: Introductionmentioning
confidence: 97%
“…in classical imaging, where baseline telescopes are used. Recently quantum sensor networks have been introduced, and shown to offer an advantage in several problems: to measure field gradients [4][5][6], to increase the accuracy of atomic clocks [7,8], or of interferometers and telescope networks [9][10][11][12] using entangled quantum states (see also [13][14][15][16][17][18][19][20][21][22][23]). Current experimental capabilities (e.g.…”
mentioning
confidence: 99%